Iklim Dan Kejadian Diare Pada Dua Kabupaten Di Sumatera Barat Tahun 2010-2014 - Yoerdy Agusmal Saputra; Defriman Djafri; Adila Kasni Astiena (POLTEKKES KEMENKES MANADO, 2021)
The number of deaths due to diarrhea caused by climate change is approximately 0.2%, and 85% of deaths among them are children. This research purposed to determine the relationship of climate with the incidence of diarrhea cases based on topography areas in two districts of West Sumatra from 2010-2014. This research used the ecological study design based on the time. Population and sample in this research was the incidence of diarrhea monthly data were recorded at the District Health Department for the years 2010-2014 (total sampling). Data sources using secondary data from District Health Department and Meteorological and Geophysics Station. The result showed that the average incidence rate of diarrhea during 2010-2014 in Pesisir Selatan and Agam District is 2,53/1000 population and 2.30/1000 population, temperature 27,73ºC and 22,18ºC, rainfall 233.71 mm and 234.21 mm, humidity 74.17% and 86,14%, and wind velocity 3.64 knots and 0,99 knots. Results of climate analysis and the incidence of diarrhea showed an insignificant relationship, in Pesisir Selatan and Agam District, so preventive activities such as improving community-based total sanitation (STBM) were still the right efforts to be carried out by the Pesisir Selatan District and Agam District Health Offices.